FInd the sum of all solutions of that satisfy the equation above.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
3 lo g 8 x = 3 lo g 2 3 x = 3 ⋅ 3 1 lo g 2 x = lo g 2 x = x = x 2 = x 2 − x − 6 = ( x − 3 ) ( x + 2 ) = x = lo g 4 ( x + 6 ) lo g 2 2 ( x + 6 ) 2 1 lo g 2 ( x + 6 ) lo g 2 ( x + 6 ) 2 1 ( x + 6 ) 2 1 x + 6 0 0 3 , − 2
Since the logarithm functions lo g 8 x and lo g 4 ( x + 6 ) are defined over positive numbers, the values of x + 6 and x are positive. Thus, − 2 is can not be the value of x implying that the value of 3 lo g 8 x = lo g 4 ( x + 6 ) satisfying is x = 3